KRONOLOGI HUNIAN PRASEJARAH DI GUA BRAHOLO DAN SONG KEPLEK, GUNUNG SEWU - Harry Truman Simanjuntak (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
Gua Braholo and Song Keplek are two of the some caves, which have been intensively excavated since 1990's. The research result shows that both caves were occupied by the prehistorically human before the Pleistocene was over. The chronology of occupancy in this area was started from the eldest (Paleolithic) to the youngest one (Paleometallic) which were separated into six periods: Baksosa, Terus, Tabuhan, Keplek, Gupuh, and Klepu. In the Gunung Sewu context, the occupancy in Gua Braholo and Song Keplek were went on from Tabuhan period, continued to Keplek period, and Gupuh period as the occupancy in the early Neolithic. The expansion from period to period be tend to gradual, there was no